Demonstrasi Memprediksi Gangguan Cerebral Pada Orang Dengan Trauma Kepala Melalui Pengukuran Tekanan Darah - Elida Sinuraya; Idahwati; Loisha Inka D (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Head injury is leading cause of death and disability. Brain cells around the injury will be functionally impaired. If the brain was widespread and bleeding, it has an impact on the failure of blood pressure controls mechanisms because blood pressure is one of the indicators in the prognosis of head injury patients. Objective: the community was able to identify blood pressure measurement, the community was able to say hello before taking blood pressure, the community was able to prepare blood pressure equipment, the community was able to preparing client before taking blood pressure, and the community was able to taking blood pressure on client. Method: a demonstration method was use in this community service. Result: the community was able to identify blood pressure measurement in good category (88.9%),, The community was able to say hello before taking blood pressure in good category (88.9%), the community was able to prepare blood pressure equipment in good category (74.1%), the community was able to prepare client before taking blood pressure in good category (74.1%),  and the community was able to taking blood pressure the very good category (63.0%). Conclusion: The activity of demonstration taking blood pressure by community to predicting cerebral disorders in people with head injury was effective